SPECIFICS OF DEVELOPING A STRUCTURAL AND FUNCTIONAL MODEL FOR FORMING GRAPHIC LITERACY OF FUTURE TEACHERS OF VOCATIONAL EDUCATION: CHARACTERISTICS OF THE MAIN ELEMENTS-BLOCKS - TYMCHUK, Andrii (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2026)
Development and design of the structural and functional model within the framework of the study are aimed at addressing a scientific and practical problem: determining the theoretical foundations and practical mechanisms for the formation of graphic literacy among future teachers of vocational education through the implementation of the blocks of the structural and functional model in the educational process of pedagogical universities. The peculiarities of designing the proposed model lie in presenting the studied process as a set of block elements, each of which defines the logic of scientific inquiry. The process of forming graphic literacy among teachers of vocational education within higher pedagogical institutions is presented in the form of a structural and functional model comprising target, theoretical-methodological, organisational-content, control-evaluative, and resultative blocks. The target block of the model is based on the requirements of state educational standards and social demand. The theoretical-methodological block of the model reflects a combination of approaches (systemic, learner-centred, activity-based, and environmental) and principles (systematicity and consistency, professional orientation, integrity, continuity, activity, self-development, unity of theory and practice, consciousness and student activity, and visualisation), which were applied within the research. The organisational-content block represents the set of stages and organisational conditions for the formation of the studied phenomenon through the creation and implementation of specialised digital educational and methodological support. The integration of digital technologies into the learning process allows for the personalisation of education and the implementation of the principle of visualisation through the use of multimedia technologies, digital learning aids, and educational video content. The control-evaluative and resultative blocks of the proposed structural and functional model include a component-criterion structure of the graphic literacy of future teachers of vocational education and the research outcomes, that is, the formation of this literacy at the defined levels. The results of the conducted work suggest that this model serves as an effective tool for resolving the identified contradictions between the demands of the digital society and the current level of graphic literacy among future teachers of vocational education. The presented structural and functional model is a scientifically grounded means of addressing the stated problem, opening up new prospects for the modernisation of teacher training in accordance with the challenges of the information age.